Population dynamics of the mangrove tree crab Aratus pisonii (Brachyura: Sesarmidae) in the estuarine complex of Cananéia-Iguape, São Paulo, Brazil - Leme, Maria Helena de Arruda; Soares, Vanessa de Sousa [UNESP]; Pinheiro, Marcelo Antonio Amaro [UNESP] (My University, 2014)
The population dynamics of Aratus pisonii in the coastal system of Cananéia-Iguape was evaluated by means of cohort analysis (Bhattacharya method), comparison of the reproductive output and size structure of the ovigerous females among months and seasons of the year. Most ovigerous females were sampled in the rainy season. A reproductive pause occurred during the dry season, when the sex ratio was biased toward females, indicating high feeding activity by this sex. Fecundity was compared between females captured in rainy and dry seasons to test the hypothesis of reproductive output seasonality in this subtropical population, a fact that was rejected. By analyses of the mean size of ovigerous females along of the months of their occurrence, it was detected two cohorts: larger (older) females start the breeding early in the spring and the smaller ones (primiparous) began their reproduction in the austral summer. Compared with other populations of A. pisonii, these crabs reached functional maturity earlier in their life cycle. Our findings reveal the response pattern of A. pisonii in a subtropical humid climate mangrove area with conditions of exceptionally high productivity.
Keywords: Estuarine crab; Fecundity; Mangrove; Population structure; Reproduction